Aspek Legalitas dalam Perlindungan Hukum Paten di Indonesia - Suwardi (Faculty of Law Hang Tuah University, 2018)
The important role in the simple patent of technology-based development is absolutely necessary to support the success of economic sector development. The functions and roles of such patents are important in supporting technological development in supporting the success in the field of technology. It is necessary to have a legal field that regulates legal protection if an invention in the field of technology is misused by another person who is not entitled to use it. The legal instruments are in the form of a patent law contained in Law Number 6 Year 1998 as amended and refined by Law Number 13 of 1997. The number of patent applications originating from within the country is 229 pieces or 1.82 percent of all patent applications. While the number of simple patent requests originating from within the country is 153 pieces or 41.02 percent of all simple patent requests. Looking at the numbers above, in the period of approximately five years since the entry into force of the UUP, it turns out that this patent registration request is still widely used by technology inventors (inventory originating from abroad (WNA), while those from within the country (Indonesian citizens) ) fewer numbers both in the field of patents and simple patents.